EVALUASI KINERJA RUAS JALAN TERHADAP PERKEMBANGAN KEGIATAN PERDAGANGAN DAN JASA DI RUAS JALAN YOSODIPURO, KOTA SURAKARTA - Dinda Ismira Setyoningtyas; Kuswanto Nurhadi; Isti Andini (ARSITEKTURA, 2015)
: Jalan Yosodipuro is a local path that connects the city of Surakarta to downtown. Jalan Yosodipuro is a strategic area close to the main line of Surakarta City, Jalan Slamet Riyadi. The development of economic activity in this streets has began since the construction of a Mall that Solo Paragon Mall. As trade and service area began to grow, commercial activities dominate land use along the road Yosodipuro complement previous activities: education and housing. Means of trade and services in the form of a shop and even the development of the home into a place of business functions are often found along Jalan Yosodipuro. The high activity in this region causes the amount of movement of the vehicle is not able to be accommodated by the existing road capacity.To overcome this problem researchers conducted a study on the evaluation of the performance of the road to the development of trading activities and services. The analytical method used in this study is the analysis of the development of trade and services activities include the development of the number of business units, floor area, extensive land use and range of activities. Analysis of changes in the performance of roads which include changes in the flow of vehicles, number of occurrences side barriers, and the capacity of the road and analysis croosstab. From the overall results of analysis show that the activity of trade and services in the Yosodipuro Road experienced growth from 2010 - 2014. The development of trade and services activities cause a disturbance in the traffic activity in  Yosodipuro Road. From the research that has been conducted found that the development of trade and services activities in road Yosodipuro large influence on changes in the side barrier and the amount of traffic flow, as well as the effect being to change the capacity of the road. Keywords: Degree of Saturation, Levels of Service, Road